Evaluation of the Local Synergistic Effect of a Dexketoprofen and Chlorhexidine Combination in the Formalin Test - Esparza-Villalpando, Vicente; Pozos-Guillén, Amaury; Zapata-Morales, Juan Ramón; Vértiz-Hernández, Antonio; Martinez-Aguilar, Victor Manuel; Chavarria-Bolaños, Daniel (Puerto Rico Health Sciences Journal, 2023)
Objective: Evidence supports the local application of non-steroidal antiinflammatory drugs such as dexketoprofen trometamol (DXT) for pain management, but little is known about the potential antinociceptive effect of chlorhexidine gluconate (CHX) and its possible synergistic effect when combined with DXT. The aim of this study was to evaluate the local effect of a DXT–CHX combination using isobolographic analysis in a formalin pain model in rats. Materials and Methods: Briefly, 60 female Wistar rats were used for the formalin test. Individual dose effect curves were obtained using linear regression. For each drug, the percentage of antinociception and median effective dose (ED50; 50% of antinociception) were calculated, and drug combinations were prepared using the ED50s for DXT (phase 2) and CHX (phase 1). The ED50 of the DXT–CHX combination was determined, and an isobolographic analysis was performed for both phases. Results: The ED50 of local DXT was 5.3867 mg/mL in phase 2 and for CHX was 3.9233 mg/mL in phase 1. When the combination was evaluated, phase 1 showed an interaction index (II) of less than 1, indicating synergism but without statistical significance. For phase 2, the II was 0.3112, with a reduction of 68.88% in the amounts of both drugs to obtain the ED50; this interaction was statistically significant (P < .05). Conclusion: DXT and CHX had a local antinociceptive effect and exhibited synergistic behavior when combined in phase 2 of the formalin model.